DO MARKET TIMING INCENTIVES AFFECT THE DEBT-EQUITY CHOICE OF MALAYSIAN SHARIAH-COMPLIANT IPOs? - Bougatef, Khemaies; Kassem, Oumaima (Bank Indonesia, 2023)
Empirical and theoretical literature points out that market timing could shape financing decisions and persistently affect capital structure. However, prior studies on market timing do not distinguish between Shariah-compliant and non-compliant firms although Shariah compliance considerations may affect market timing incentives. This paper aims to fill this gap in the literature by investigating whether market timing theory is relevant in the case of Shariah-compliant firms. We consider panel data consisting of 40 Malaysian Shariah-compliant companies that went public during the period from 1 January 2015 to 31 December 2018. We report evidence that managers of Malaysia Shariah-compliant IPOs tend to time the market by issuing equity when they perceive that their shares are overpriced and market conditions are favorable. However, the impact of these market timing on their capital structure quickly disappears. The findings provide useful implications for investors and portfolio managers interested in investing in Shariah-compliant IPOs. They should identify market timers in order to avoid low subsequent returns of equity issuers.